Modeling the Impact of Cotton Production on Economic Development in Benin: A Technological Innovation Perspective - Chabi Simin Najib, Dafia; Fei, Chen; Dilanchiev, Azer; Romaric, Samson (Frontiers in Environmental Science, 2022)
This research provides an in-depth understanding of cotton production in Benin. The analysis explored the effects of cotton production on economic growth using a vector error correction model (VECM). Prior to the VECM, a descriptive analysis was conducted on a time series database collated over 56 years (1965–2021) from national and international organizations including World Bank, the United States Department of Agriculture, and the National Accounts. Depending on the availability of the information over this period, the data were trimmed down to enable a better overview of the trend for variable of interest. Thus, the review of the trend for agricultural land (hectares) for cotton observed from 1965 to 2021 revealed that the trend evolves over the years in three different patterns, while the yields demonstrate four patterns over the same period. For the VECM analysis that permits to understand the long- and short-term relation, the time bound covers 30 years from 1990 to 2019 given the availability of data for all the variables used for the model. The findings highlighted that a strong and positive connection is found between cotton export and economic growth and a long-term relation between the human capital and the economic growth in Benin. A rapid human capital development will increase quality of the employment generation, and the country’s economy will adjust upward. Furthermore, a short-run coefficient unveils feedback necessary in a relative level of investment to bring back the economic growth to equilibrium. From these findings discussed in this study, the government of Benin is commended to diversify the production of cotton through a town target policy.